Bridging the gap: evaluating high TB burden country data needs to support the potential introduction of TB vaccines for adolescents and adults: a workshop report - Clark, Rebecca A.; Young, Carly; Palmer, Shaun; Auma, Erick; Malhotra, Shelly; Limaye, Rupali; Giersing, Birgitte; Schrager, Lewis; Voss, Gerald; Tiemersma, Edine; Frick, Mike; Edoka, Ijeoma; et al. (Frontiers in Tuberculosis, 2024)
High tuberculosis (TB) burden countries (HBCs) need to prepare for TB vaccine implementation alongside licensure, to ensure rapid rollout. WHO policy/implementation frameworks have been created to support this effort. Using WHO frameworks, we convened a workshop to ask HBC experts about what epidemiological, impact, feasibility and acceptability data they anticipated they would need to guide TB vaccine introduction. For required data, we asked HBC and global experts which data were already available, data collection planned, or gaps.HBC experts expressed high demand for epidemiological, impact, feasibility and acceptability data, reported variable availability of existing epidemiological data, and low availability for impact, feasibility, and acceptability data. Global experts reported additional knowledge of existing data on impact, upcoming collection of infection prevalence, acceptability and feasibility data, and potential epidemiological data collection on adolescents, adults, people living with HIV, and underweight individuals.HBC and global experts made key recommendations for: a coordinated data collation, collection, analysis and sharing system; updating existing HBC health and economic impact estimates and extending impact analyses to other HBCs; demand/market forecasting; resource gap mapping; aligning delivery strategies; addressing manufacturing, procurement, delivery, and regulatory barriers; sharing potential vaccine licensure timing; incorporating TB vaccine introduction strategies into NSPs, immunization programs, and health services; collecting vaccine hesitancy, mistrust, and misinformation data; collecting adolescent/adult vaccine demand generation data, and identifying funding.Experts recommended expanding this analysis to other areas of the WHO frameworks, including more HBC stakeholders, and repeating this analysis after country and community advocacy and socialization around different vaccine candidates.